Sedation AND Weaning In Children (SANDWICH): protocol for a cluster randomised stepped wedge trial. Issue 11 (10th November 2019) - Blackwood, Bronagh; Agus, Ashley; Boyle, Roisin; Clarke, Mike; Hemming, Karla; Jordan, Joanne; Macrae, Duncan; McAuley, Daniel Francis; McDowell, Clíona; McIlmurray, Lisa; Morris, Kevin P; Murray, Margaret; et al.
Abstract : Introduction: Weaning from ventilation is a complex process involving several stages that include recognition of patient readiness to begin the weaning process, steps to reduce ventilation while optimising sedation in order not to induce distress and removing the endotracheal tube. Delay at any stage can prolong the duration of mechanical ventilation. We developed a multicomponent intervention targeted at helping clinicians to safely expedite this process and minimise the harms associated with unnecessary mechanical ventilation. Methods and analysis: This is a 20-month cluster randomised stepped wedge clinical and cost-effectiveness trial with an internal pilot and a process evaluation. It is being conducted in 18 paediatric intensive care units in the UK to evaluate a protocol-based intervention for reducing the duration of invasive mechanical ventilation. Following an initial 8-week baseline data collection period in all sites, one site will be randomly chosen to transition to the intervention every 4 weeks and will start an 8-week training period after which it will continue the intervention for the remaining duration of the study. We aim to recruit approximately 10 000 patients. The primary analysis will compare data from before the training (control) with that from after the training (intervention) in each site. Full details of the analyses will be in the statistical analysis plan. Ethics and dissemination: This protocol was reviewed and approved by NRES Committee East Midlands—Nottingham 1 Research Ethics Committee (reference: 17/EM/0301). All sites started patient recruitment on 5 February 2018 before randomisation in April 2018. Results will be disseminated in 2020. The results will be presented at national and international conferences and published in peer-reviewed medical journals. Trial registration number: ISRCTN16998143 .